Institutions, governance and extractives: Where politics and ecologies collide - Beban A; Banks G (Elsevier B.V., 2023)
Provides an introduction to the Special Issue: Politics and Ecologies. We review recent literature on the political ecology of extraction, and on relational approaches within the field. The introduction then provides a brief precise of each paper and their contribution, as well as the contribution of the collection to the field.
Keywords: Political Ecology; Extractive Industries; Relational approaches